Hierarchical gallium nitride / nitrogen-doped carbon composites and methods of making the same
Patent Information
- Application Number
- CN202310359404.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-03-31
AI Technical Summary
然而,上述方法存在制备过程繁琐、难以规模化量产、所得氮化镓基电极材料比表面小、界面储能比容量低的缺点
[0025]1、本发明提供的一种分级结构氮化镓/氮掺杂碳复合物的制备方法,过程简单,环境友好,易于规模化工业生产。
Smart Images

Figure CN116469697B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage technology, and relates to a method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite and its application in the field of supercapacitors. Background Technology
[0002] Supercapacitors possess high specific power and relatively high specific energy, making them a type of electrochemical energy storage device that falls between traditional dielectric capacitors and batteries (Science, 2008, 321, 651-652). The future development direction of supercapacitors is to increase specific energy without compromising specific power and cycle life. This requires supercapacitor electrode materials to possess high conductivity, high ion migration rate, high ion-accessible surface area, and high electrochemical stability (Nature Communications, 2014, 5, 4554). To achieve this goal, previous researchers have designed a variety of electrode materials with porous structures, such as two-dimensional porous structures (Science 2012, 335, 1326–1330; Advanced Energy Materials, 2016, 6, 1501115; Advanced Materials, 2019, 31, e1902393), three-dimensional porous structures (Nature Reviews Materials, 2018, 4, 45-60), and two-dimensional materials arranged vertically (Nature, 2018, 557, 409-412; Advanced Materials, 2015, 27, 4566-4571).
[0003] Hierarchical porous materials consist of interconnected yet relatively independent structures in two-dimensional or multi-scale spaces, possessing a large specific surface area and abundant pore structure, which is beneficial for electrolyte penetration and the regulation of volume shrinkage / expansion during charge and discharge (Advanced Energy Materials, 2018, 8, 1701415; Advanced Functional Materials, 2012, 22, 4634-4667). Hierarchical structures combine the advantages of fast electrode reaction kinetics of nanomaterials and high packing density of micromaterials, enabling electrodes to simultaneously possess high rate capability and high volumetric energy density (Advanced Energy Materials, 2018, 8, 1701415). However, research on hierarchical metal nitrides in the field of electrochemical energy storage is rarely reported in the literature (Nano-Micro Letters, 2018, 10, 63).
[0004] As a third-generation semiconductor material, gallium nitride (GaN) has been extensively studied in the field of electrochemical energy storage. To improve the electrochemical performance of GaN-based electrode materials, previous researchers have developed various methods. For example, electrochemical etching is used to prepare mesoporous films (Advanced Materials, 2016, 28, 3768-3776), template methods are used to prepare nanosheets (ACS Applied Materials Interfaces 2017, 9, 26631-26636), chemical vapor deposition is used to prepare nanowires (Small 2017, 13, 1603330), electrosimulation is used to prepare GaN / carbon nanowire composites (ACS Applied Materials Interfaces, 2019, 11, 44263-44269), and amorphous GaN is deposited on a three-dimensional metal framework (Advanced Functional Materials, 2017, 27, 1701808). However, the above methods have drawbacks such as complicated preparation process, difficulty in large-scale mass production, small specific surface area of gallium nitride-based electrode materials, and low interfacial energy storage capacity. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite, which, when used as an electrode material for supercapacitors, exhibits excellent electrochemical performance.
[0006] A method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite is characterized by: using gallium trichloride as the gallium source and melamine as the nitrogen source, employing a carbothermal reduction method in a closed system, and controlling the heat treatment time to regulate the structure of gallium nitride and the relative content of gallium nitride and carbon components, thereby regulating the electrochemical performance of the hierarchical gallium nitride / nitrogen-doped carbon composite electrode.
[0007] Carbothermic reduction is a redox reaction method that uses inorganic carbon as a reducing agent and is carried out at a certain temperature. This reaction requires a relatively high temperature.
[0008] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0009] a. Melamine and GaCl3 solution are ground and mixed in a fume hood to obtain mixture A.
[0010] b. Transfer mixture A to a reactor, purge it with nitrogen, and then seal it; then transfer it to a tubular furnace.
[0011] c. Under nitrogen protection, heat the tube furnace to the reaction temperature, hold for 6–9 hours, and then cool naturally to room temperature to obtain gallium nitride / nitrogen-doped carbon composite.
[0012] The gallium trichloride and melamine mentioned in step a, wherein the molar ratio of gallium trichloride to melamine is 1:1 to 1:3.
[0013] The GaCl3 solution mentioned in step a is preferably a GaCl3-benzene solution. Benzene is used to dissolve gallium chloride for ease of use, and there is no particular limitation on the solution concentration.
[0014] Preferably, in step b, mixture A is transferred to a reactor lined with graphite paper, which serves as a substrate to prevent the reactants from directly contacting the reactor wall.
[0015] The reaction temperature in step c is 800-850℃, the time is 6-9 hours, and the heating rate is 5-10℃ / min. -1 .
[0016] This invention also provides gallium nitride / nitrogen-doped carbon composites prepared by the above method, wherein the gallium nitride / nitrogen-doped carbon composites are composed of gallium nitride and nitrogen-doped carbon, and their FT-IR spectra are located at 1574, 1400 and 1180–1215 cm⁻¹. –1 The peaks correspond to the C=C / C=N stretching vibration, CO–H / CN–H deformation vibration, and C–O / C–N stretching vibration, respectively. The peaks at 394.25±0.15, 397.05±0.05, 398.0, 398.7±0.1, 399.8, and 401.0 eV in the N 1s spectrum are attributed to N defects, N-Ga, pyridine N, N-Ga-O, pyrrole N, and graphitized N components, respectively.
[0017] Raman spectra located in the 100-900 and 1000-1800 cm⁻¹ -1 The peaks are attributed to the characteristic peaks of gallium nitride and carbon components, respectively. These peaks are located at 145, 532, 561, and 711 cm⁻¹. -1 The peaks are attributed to the E2(low), A1(TO), E1(TO), and A1(LO) Raman vibration modes of gallium nitride, respectively.
[0018] Preferably, the gallium nitride / nitrogen-doped carbon composites all have a hierarchical structure. The gallium nitride / nitrogen-doped carbon composites are mainly composed of gallium nitride micron-sized clusters (gallium nitride microclusters), which are formed by stacking gallium nitride nanowires (with a diameter of 30-70 nm). The gallium nitride microclusters form porous gallium nitride microclusters due to thermal decomposition.
[0019] The pore distribution curves of the gallium nitride / nitrogen-doped carbon composite samples indicate that ( Figure 3 b) The gallium nitride / nitrogen-doped carbon composite sample has hierarchical pores with pore sizes of 0.8, 1.4, 1.7, 2.8, 3.9, 7.7 and 10.8 nm.
[0020] The relative content of gallium nitride and carbon components in the gallium nitride / nitrogen-doped carbon composite, wherein the mass percentage of carbon component in the composite is 8-14%.
[0021] The present invention also provides the application of the gallium nitride / nitrogen-doped carbon composite for use as a working electrode in a supercapacitor.
[0022] The gallium nitride / nitrogen-doped carbon composite electrode, wherein the loading of the gallium nitride / nitrogen-doped carbon composite (active material) is 3-9 mg cm⁻¹. -2 ;
[0023] The electrochemical performance of the gallium nitride / nitrogen-doped carbon composite electrode, wherein, at 200 mA cm⁻¹, -2 Below, the electrode active material loading is 3-4 mg cm⁻¹ -2 At that time, the discharge specific capacity of the electrode area was 110-310 mF cm⁻¹. -2 .
[0024] Beneficial effects
[0025] 1. The present invention provides a method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite, which is simple, environmentally friendly, and easy to scale up for industrial production.
[0026] 2. The present invention provides a method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite, which not only allows for the control of the structure of gallium nitride and the relative content of gallium nitride and nitrogen-doped carbon, but also provides gallium nitride-based electrode materials for high-performance supercapacitors, achieving high performance at 200 mA cm⁻¹. -2 At high current densities, the hierarchical gallium nitride / nitrogen-doped carbon composite (with a loading of 3-4 mg cm⁻¹) -2 The area discharge specific capacity is 110-310 mF cm⁻¹. -2 . Attached Figure Description
[0027] Figure 1 Spectra of the samples: (a) XRD; (b) Raman; (c) FT-IR; (d) N1s electronic spectrum.
[0028] Figure 2 SEM images of the samples: (a) S-1; (b) S-2; (c) S-3; (d) S-4.
[0029] Figure 3 (a) Nitrogen adsorption-desorption isotherm; (b) Pore distribution curve.
[0030] Figure 4 Loading capacity is 3-4 mg cm -2Electrochemical performance of the lower electrode: (a) CVs; (b) GCD curve; (c) rate capability; (d) cycle performance.
[0031] Figure 5 S-3 at a loading of 7.6 mg cm -2 Electrochemical performance of the lower electrode: (a) GCD curve; (b) rate capability.
[0032] Figure 6 Electrochemical performance of the S-3∥S-3 symmetrical supercapacitor device: (a) CVs; (b) GCD curves; (c) cycling performance; (d) volumetric specific energy-specific power plot; single electrode active material loading is 7.6 mg cm⁻¹ -2 . Detailed Implementation
[0033] The technical solution of the present invention will be further described below through specific embodiments and in conjunction with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and should not be regarded as limiting the content of the claims of the present invention.
[0034] In the examples, benzene and N-methylpyrrolidone were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; stainless steel wire mesh, acetylene black, and polyvinylidene fluoride were purchased from Jinghong New Energy on Taobao; BH5510 sulfonated diaphragm was purchased from Shenzhen Gebang Technology Co., Ltd.; gallium trichloride was prepared by the combustion reaction of metallic gallium with chlorine.
[0035] X-ray powder diffraction (XRD) spectra were obtained using a Bruker D8 Advance powder diffractometer (Germany); scanning electron microscopy (SEM) images and elemental distribution maps were obtained using a Hitachi Regulus 8220 field emission scanning electron microscope (Japan); Raman spectra were obtained using a HORIBA Scientific LabRAM HR Evolution Raman spectrometer (France); Fourier transform infrared (FT-IR) spectra were obtained using a Nicolet 10 infrared spectrometer (USA); and X-ray photoelectron spectroscopy (XPS) spectra were obtained using a Fisher Scientific ESCALAB Xi... + X-ray photoelectron spectroscopy was used to obtain the nitrogen adsorption-desorption isotherms and pore size distribution, which were obtained using a Micromeritics ASAP 2460 fully automated surface area and pore size analyzer.
[0036] The electrochemical performance of the sample electrodes was obtained using a Shanghai Chenhua CHI760E electrochemical analyzer. The active material loading of the sample electrodes was 3–9 mg / cm³. –2 The current collector is made of stainless steel wire mesh, the diaphragm is a BH5510 sulfonated diaphragm, and the electrolyte is 1 mol / L. –1H2SO4; In the three-electrode system, the counter electrode is a platinum sheet, and the reference electrode is Hg / Hg2SO4.
[0037] Example 1
[0038] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0039] a. Mix 1.51g of melamine with 4mL of 1mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0040] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0041] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 6 hours and then naturally cooled to room temperature to obtain sample S-1.
[0042] Example 2
[0043] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0044] a. Mix 1.51g of melamine with 4mL of 1mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0045] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0046] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 7 hours and then naturally cooled to room temperature to obtain sample S-2.
[0047] Example 3
[0048] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0049] a. Mix 1.51g of melamine with 4mL of 1mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0050] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0051] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 8 hours and then naturally cooled to room temperature to obtain sample S-3.
[0052] Example 4
[0053] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0054] a. Mix 1.51g of melamine with 4mL of 1mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0055] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0056] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 9 hours and then naturally cooled to room temperature to obtain sample S-4.
[0057] Example 5
[0058] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0059] a. Mix 0.504 g of melamine with 4 mL of 1 mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0060] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0061] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 8 hours and then naturally cooled to room temperature to obtain sample S-5.
[0062] Example 6
[0063] The preparation of a hierarchical gallium nitride / nitrogen-doped carbon composite involves the following steps:
[0064] a. Mix 1.01g of melamine with 4mL of 1mol L... -1 The GaCl3–benzene solution was ground and mixed in a fume hood to obtain mixture A.
[0065] b. Transfer mixture A to a stainless steel reactor lined with graphite paper, purge it with nitrogen, and then seal it; then transfer it to a tube furnace.
[0066] c. Under nitrogen protection, heat the tube furnace to 800℃ at a heating rate of 10℃ / min. –1 The sample was kept at 800℃ for 8 hours and then naturally cooled to room temperature to obtain sample S-6.
[0067] Results Analysis
[0068] Figure 1 a is the XRD pattern of the sample. From Figure 1 As can be seen, S-1 and S-2 exhibit good crystallinity, with each diffraction peak in S-1 and S-2 corresponding to the (100), (002), (101), (102), (110), (103), (200), (112), and (201) crystal planes of hexagonal gallium nitride (PDF#50-0972), respectively. In S-3, the intensity of diffraction peaks related to gallium nitride decreases significantly, while the diffraction peaks related to carbon (the diffraction peak at 26.4° corresponds to the (002) crystal plane of hexagonal graphite PDF#14-1487) are significantly enhanced. In S-4, the diffraction peaks related to gallium nitride almost disappear, while the carbon peak at 26.4° is clearly distinguishable. These results indicate that the crystallinity of gallium nitride gradually decreases with prolonged heat treatment time, which is attributed to the structural damage caused by the thermal decomposition of gallium nitride; while the relative enhancement of the carbon diffraction peak intensity is attributed to the gradual increase in the graphitization degree of the carbon component.
[0069] Raman spectroscopy can reveal more structural information about a sample. Figure 1 b). Raman spectra located at 100-900 and 1000-1800 cm⁻¹ -1 The peaks are attributed to the characteristic peaks of gallium nitride and carbon components, respectively. These peaks are located at 145, 532, 561, and 711 cm⁻¹. -1 The peaks were attributed to the E2(low), Al(TO), E1(TO), and Al(LO) Raman vibration modes of gallium nitride (Chemical Physics Letters, 2001, 345, 245-251). As the heat treatment time exceeded 7 hours, the characteristic Raman peaks of gallium nitride gradually weakened, while the Raman peaks of carbon gradually strengthened, which is consistent with the results of the sample XRD. Furthermore, the peaks located at 580–680 cm⁻¹... –1 The peak at this location is related to the lattice disorder of gallium nitride (Semicond. Sci. Technol., 2002, 17, 1223-1225). It can be seen that as the heat treatment time exceeds 6 hours, the Raman peak at this location gradually becomes more obvious. This indicates that the lattice disorder of gallium nitride increases with the extension of reaction time.
[0070] The coexistence of gallium nitride and carbon components in the sample can be verified by infrared spectroscopy. Figure 1 c). The FT-IR spectra are located at 1574, 1400, and 1180–1215 cm⁻¹.–1 The peaks correspond to the C=C / C=N stretching vibration, CO–H / CN–H deformation vibration, and C–O / C–N stretching vibration, respectively (Applied Catalysis A: General, 2012, 439-440, 149-155). This indicates that the carbon component in the sample is nitrogen-doped carbon. The peaks are located at 480–750 cm⁻¹. –1 The peak is attributed to the ω of hexagonal gallium nitride. T Phonon mode (Journal of Materials Research, 2000, 15, 267-269): The intensity of this peak gradually weakens with the extension of heat treatment time, which is attributed to the gradual thermal decomposition of gallium nitride.
[0071] Table 1 N 1s peak separation results
[0072]
[0073] The coexistence of gallium nitride and carbon components in the sample was further verified by XPS spectra. Figure 1 d). Peaks at 394.25±0.15, 397.05±0.05, 398.0, 398.7±0.1, 399.8, and 401.0 eV in the N 1s spectrum are attributed to N defects, N-Ga, pyridine N, N-Ga-O, pyrrole N, and graphitized N components, respectively (Advanced Materials, 2016, 28, 3768-3776; Chem. Eur. J., 2015, 21, 324-330; Journal of Materials Chemistry A, 2015, 3, 21257-21268). Due to the thermal decomposition of gallium nitride, the content of gallium nitride-related components (N-Ga, N-Ga-O) gradually decreases with increasing heat treatment time, while the content of carbon-related components (pyridine N, pyrrole N, and graphitized N) gradually increases (Table 1). Pyridine N and pyrrole N are different forms of N in carbon materials.
[0074] The above spectroscopic characterization results show that: (1) the composite provided by this invention is composed of gallium nitride and nitrogen-doped carbon; (2) with the increase of heat treatment time, the gallium nitride structure is gradually destroyed due to thermal decomposition, and the component content gradually decreases, while the graphitization degree of carbon gradually increases, and the component content gradually increases. Through further thermogravimetric analysis, the mass percentage content of carbon components in the composites of S-1, S-2, S-3 and S-4 was determined to be 8.58%, 8.72%, 9.11% and 13.55%, respectively.
[0075] Figure 2The image shows the SEM images of the samples. As can be seen from the images, all samples exhibit a hierarchical structure. S-1 is mainly composed of gallium nitride micron-sized clusters, which in turn are composed of nanowires. Figure 2 a); where the thinner end of the microcluster cluster consists of relatively separated nanowires with a diameter of 30–70 nm, and the thicker end consists of closely packed nanowires. Pores caused by the thermal decomposition of gallium nitride are clearly visible in the gallium nitride microclusters in S-2. Figure 2 b). When the heat treatment time is increased to 8 hours, gallium nitride microclusters form a honeycomb structure due to thermal decomposition. Figure 2 c); As the heat treatment time increases to 9 hours, the honeycomb structure collapses, forming a porous stacked structure. Figure 2 d). SEM results show that the morphology of the sample can be controlled by adjusting the heat treatment time.
[0076] By controlling the heat treatment time, not only the morphology and composition of the sample can be adjusted, but also its textural properties can be controlled. Figure 3 The nitrogen adsorption-desorption test results of the sample showed that ( Figure 3 a) The sample contains micropores, mesopores, and macropores, and the S of the sample increases with the extension of heat treatment time. BET The pore size gradually increases. The pore distribution curve of the sample shows that ( Figure 3 (b) The sample exhibits hierarchical pores with pore sizes ranging from 0.8 to 10.8 nm. As the heat treatment time increases from 6 h to 8 h, mesopores gradually decrease, while micropores at 1.4 nm gradually increase; however, with a heat treatment time of 9 h, mesopores with a pore size of 2.8 nm become dominant. Nitrogen adsorption-desorption results indicate that controlling the heat treatment time can regulate the So of the sample. BET Pore distribution and pore volume (Table 2).
[0077] Table 2. Texture properties of the samples
[0078]
[0079]
[0080] Table 3. Area discharge specific capacity of sample electrodes at different current densities.
[0081]
[0082] Porous gallium nitride / nitrogen-doped carbon samples with hierarchical structures exhibit excellent electrochemical performance when used as electrode materials for supercapacitors. Figure 4 ). Figure 4 a represents the sample electrode at 10 mV s –1The cyclic voltammetry (CV) curves below show that the near-rectangular CV curves indicate that the interfacial energy storage of the sample electrode is mainly due to the electrochemical double-layer (EDLC) capacitance. The redox peaks in the CV curves are attributed to the Faraday reactions occurring on the electrode surface. The distance between the oxidation and reduction peaks is only 27-58 mV, indicating that the Faraday reactions on the sample electrode surface are reversible.
[0083] The specific capacity of the sample electrode can be calculated from the galvanostatic charge-discharge (GCD) curve. At 1 mA cm⁻¹ -2 At current densities, the sample electrodes S-1, S-2, S-3, and S-4 (active material loading of 3–4 mg cm⁻¹) –2 The areal discharge specific capacities were 129, 275, 448, and 389 mF / cm, respectively. -2 ( Figure 4 b). The sample electrode not only exhibits high specific capacity at low current densities, but also good rate performance. Figure 4 c. Table 3). When the current density increases from 1 mA cm⁻¹ -2 Increased to 200mA cm -2 The capacity retention rates of electrodes S-1, S-2, S-3, and S-4 were 60.8%, 58.2%, 60.3%, and 69.2%, respectively. The higher rate performance of electrodes S-1, S-2, and S-4 is attributed to the hierarchical and porous structure of the samples, while the superior rate performance of electrode S-3 is attributed to its unique honeycomb structure, which not only facilitates ion migration but also helps regulate volume expansion and contraction during charge and discharge (Advanced Functional Materials, 2012, 22, 4634-4667). At 10 mA cm⁻¹ -2 After 10,000 cycles, the capacity retention of electrodes S-1, S-2, S-3, and S-4 was close to 100%. Figure 4 d) demonstrates excellent electrochemical cycling stability.
[0084] As shown in Table 3, S-3 exhibits the best overall performance. It should be noted that when the molar ratio of gallium trichloride to melamine is 1:1 (S-5) and 1:2 (S-6), the specific capacity and rate capability of the sample electrodes are both relatively ideal (Table 3). Rate capability is the ratio of the discharge specific capacity at high current density to the discharge specific capacity at the initial low current density; a higher ratio indicates a better rate capability.
[0085] The electrode provided by this invention not only has a low loading of active material (3–4 mg cm⁻¹), but also... –2 It exhibits excellent rate performance at high active material loadings, and its rate performance remains excellent even at high active material loadings. Taking the S-3 electrode as an example, when the active material loading is 7.6 mg / cm³... –2 At 1mA cm-2 The area discharge specific capacity is 1076 mF cm⁻¹ -2 At 200mAcm -2 The area discharge specific capacity is 730 mF cm⁻¹ -2 ( Figure 5 The capacity retention rate was 67.8%. The active substance loading was 9.0 mg / cm³. –2 At 1mA cm -2 The area discharge specific capacity is 1096 mF cm⁻¹ -2 At 200mA cm -2 The area discharge specific capacity is 540 mF cm⁻¹ -2 The capacity retention rate was 49.3%.
[0086] Example 7
[0087] Assembly of S-3∥S-3 symmetrical supercapacitor
[0088] 1) Take an appropriate amount of S-3 powder, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add an appropriate amount of N-methylpyrrolidone, grind thoroughly to obtain a slurry;
[0089] 2) The slurry is evenly coated on the stainless steel wire mesh (current collector), and then placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain the working electrode.
[0090] 3) Using 1 mol L –1 H2SO4 is used as the electrolyte, BH5510 sulfonated diaphragm is selected, and R2032 button-type symmetrical supercapacitor is assembled.
[0091] Results Analysis
[0092] Figure 6 a represents a supercapacitor device (single electrode active material loading of 7.6 mg cm⁻¹). –2 The CV plot of the sample when the scan rate reaches 500 mV / s -1 At that time, CV can still maintain a rectangular shape. Figure 6 b represents the GCD curve of the device, with a current density of 50 mA cm⁻¹. –2 At this time, the device's GCD curve still maintains an almost isosceles triangle shape. CV and GCD test results indicate that the device exhibits excellent rate performance. At 10-50 mA cm⁻¹ –2 The current density was continuously varied within the range for 20,000 cycles and then returned to 10 mA cm⁻¹. –2 500 cycles ( Figure 6 c) The device retains 98.1% of its capacity, demonstrating excellent electrochemical cycling stability. The device achieves a volumetric power specific of 142.9 mW / cm².-3 At that time, the volumetric specific energy was 3.89 mW h cm⁻¹ -3 ; specific power is 7142.9 mW cm -3 It still has a high volumetric energy density (1.98 mW h cm⁻¹). -3 ).
[0093] The hierarchical gallium nitride-based symmetric supercapacitor provided by this invention exhibits superior volumetric energy density and specific power compared to supercapacitors based on TiN (Advanced Science 2016, 3, 1500299), TiN-Fe2N (Advanced Materials, 2015, 27, 4566-4571), GON@carbon cloth (Chemical Engineering Journal, 2021, 411, 128481), GaN nanowires@graphite paper (Small, 2017, 13, 1603330), and GaN mesoporous films (Advanced Materials, 2016, 28, 3768-3776). Figure 6 d).
[0094] In summary, this invention utilizes a carbothermal reduction reaction in a closed system to prepare a hierarchical gallium nitride / nitrogen-doped carbon composite. This composite, used as an electrode material for supercapacitors, exhibits excellent areal capacitance, rate capability, and electrochemical stability. Symmetrical supercapacitors based on the hierarchical gallium nitride / nitrogen-doped carbon composite demonstrate superior volumetric energy density and specific power. The hierarchical gallium nitride / nitrogen-doped carbon composite shows promising application prospects in the field of electrochemical energy storage and fast charging.
Claims
1. A method for preparing a hierarchical gallium nitride / nitrogen-doped carbon composite, characterized in that, The steps are as follows: a. Melamine and GaCl3 solution were ground and mixed in a fume hood to obtain mixture A; b. Transfer mixture A to a reactor, seal it after nitrogen purging, and then transfer it to a tube furnace; c. Under nitrogen protection, heat the tube furnace to the reaction temperature, hold for 6-9 h, and cool naturally to room temperature to obtain gallium nitride / nitrogen-doped carbon composite. The gallium nitride / nitrogen-doped carbon composites all have hierarchical structures. The gallium nitride / nitrogen-doped carbon composites are mainly composed of gallium nitride micron-sized clusters. The gallium nitride micron-sized clusters are formed by the stacking of gallium nitride nanowires. The gallium nitride micron-sized clusters form porous gallium nitride micron-sized clusters due to thermal decomposition.
2. The preparation method according to claim 1, characterized in that, The gallium trichloride and melamine mentioned in step a, wherein the molar ratio of gallium trichloride to melamine is 1:1 to 1:
3.
3. The preparation method according to claim 1, characterized in that, The reaction temperature in step c is 800-850 ℃, the reaction time is 6-9 h, and the heating rate is 5-10 ℃ min. -1 .
4. The gallium nitride / nitrogen-doped carbon composite prepared by the preparation method according to any one of claims 1 to 3, characterized in that, Gallium nitride / nitrogen-doped carbon composites consist of gallium nitride and nitrogen-doped carbon.
5. The gallium nitride / nitrogen-doped carbon composite as described in claim 4, characterized in that, The FT-IR spectra are located at 1574, 1400, and 1180–1215 cm⁻¹. –1 The peaks correspond to the C=C / C=N stretching vibration, CO–H / CN–H deformation vibration, and C–O / C–N stretching vibration, respectively; the peaks at 394.25 ± 0.15, 397.05 ± 0.05, 398.0, 398.7 ± 0.1, 399.8, and 401.0 eV in the N 1s spectrum are attributed to N defects, N-Ga, pyridine N, N-Ga-O, pyrrole N, and graphitized N components, respectively. Raman spectra located in the 100-900 and 1000-1800 cm⁻¹ regions -1 The peaks are attributed to the characteristic peaks of gallium nitride and carbon components, respectively; among them, the peaks located at 145, 532, 561, and 711 cm⁻¹ are characteristic peaks of gallium nitride and carbon components, respectively. -1 The peaks are attributed to gallium nitride. E 2 (low) A 1(TO) E 1(TO)and A 1(LO) Raman vibration mode.
6. The gallium nitride / nitrogen-doped carbon composite as described in claim 4, characterized in that, Gallium nitride micron-sized clusters are formed by stacking gallium nitride nanowires with a diameter of 30-70 nm.
7. The gallium nitride / nitrogen-doped carbon composite as described in claim 4, characterized in that, The gallium nitride / nitrogen-doped carbon composite exhibits hierarchical pores with pore sizes ranging from 0.8 to 10.8 nm.
8. The gallium nitride / nitrogen-doped carbon composite as described in claim 4, characterized in that, The relative content of gallium nitride and carbon components in the gallium nitride / nitrogen-doped carbon composite is 8-14% by mass.
9. The application of the gallium nitride / nitrogen-doped carbon composite according to any one of claims 4-8, or the application of the gallium nitride / nitrogen-doped carbon composite prepared by the preparation method according to any one of claims 1-3, for use as a working electrode of a supercapacitor.
10. The application as described in claim 9, characterized in that, The working electrode of the supercapacitor is a gallium nitride / nitrogen-doped carbon composite working electrode, wherein the loading of the gallium nitride / nitrogen-doped carbon composite is 3-9 mg cm⁻¹. -2 ; The electrochemical performance of the working electrode of the supercapacitor, wherein, at 200 mA cm⁻¹ -2 The electrode active material loading was 3-4 mg cm⁻¹. -2 At that time, the specific discharge capacity of the electrode area was 110-310 mF cm⁻¹. -2 .
Citation Information
Patent Citations
Manufacturing method of metal nitride film
JP2020147464A